Computer-assisted posterior instrumentation of the cervical and cervico-thoracic spine - Richter, Marcus (Springer-Verlag, 2003)
Posterior instrumentation of the cervical spine has become increasingly popular in recent years. Dissatisfaction with lateral mass fixation, especially at the cervico-thoracic junction, has led spine surgeons to use pedicle screws. The improved biomechanical stability of pedicle screws and transarticular C1/2 screws allows for shorter instrumentations and improves the repositioning possibilities. Nevertheless, there are potential risks of iatrogenic damage to the spinal cord, nerve roots or the vertebral artery with both techniques. Therefore, the aim of this study was to evaluate whether C1/2 transarticular screws and transpedicular screws can be applied safely and with high accuracy in the cervical spine and the cervico-thoracic junction using a computer-assisted surgery system (CAS system). Posterior instrumentation was performed using the Brainlab VectorVision System (BrainLAB , Heimstetten, Germany) in 19 patients. Surface matching was used for registration. We placed 22 transarticular screws C1/2, 31 cervical pedicle screws, 10 high thoracic pedicle screws and one lateral mass screw C1. The screw position was evaluated postoperatively using CT with multiplanar reconstruction in the screw axis of each screw. None of the transarticular screws or pedicle screws was significantly (>2 mm) misplaced and no screw-related injury to vascular, neurogenic or bony structures was observed. No screw revision was necessary. The mean operation time was 144 min (90–240 min) and the mean blood loss was 234 ml (50–800 ml). C1/2 transarticular screws, as well as transpedicular screws in the cervical spine and the cervico-thoracic junction, can be applied safely and with high accuracy using a CAS system. Computer-assisted instrumentation is recommended especially for pedicle screws at C3–C6.